Industrial Clusters as Source of Prospering Regions? Economic Structure and Regional Performance 2002-2007 - Alexander Kubis; Mirko Titze; Matthias Brachert (European Regional Science Association (ERSA), 2010)
This paper explores the impact of industrial clusters on regional growth at level of German labour market regions within a regional convergence model. It focuses on vertically connected industrial sectors, which can emerge parallel to horizontal interconnections. Based on works of Schnabl (2000) it is possible to identify three different effects of industrial clusters on regional economic performance. Beside the effects of regionally concentrated economic sectors (horizontal clusters) and value-added production chains (vertical clusters) on the region itself, the paper segregates regional spillover effects of industrial clusters. Furthermore, the study allows the isolated examination of the impact of industrial clusters while taking regional convergence into consideration. In addition to the all-German process of convergence and the specific East German process, positive growth effects of industrial clusters are detected. Therefore industrial clusters present an opportunity to explain deficits within the process of East-West convergence. The relative absence of industrial clusters in East Germany influences the growth potential in a negative way.
Keywords: R11; L14; 330; Convergence; Industrial Cluster